Translator Knowledge and Skills in the Era of Globalization: - Feni Natasya Silaban; Limbong, Yolanda Zefanya; Jessica Youevra Ginting; M. Rafif Zaki Ramadhan; Rina Trie Syahputri; Jhon Nicholas Giles (Pascasarjana Universitas HKBP Nommensen, 2025)
The translation profession has undergone a significant transformation in the era of globalization and technological advancement. This literature review explores how translator competencies have evolved in response to the increasing integration of digital technologies and the growing demand for cultural mediation. Drawing on 20 recent scholarly works published between 2021 and 2025, the study identifies key changes in translator knowledge and skills, including the integration of computer-assisted translation tools, post-editing of machine translation, and the need for specialization in specific fields. Additionally, the study examines how translator training programs in higher education have adapted to meet these new demands by incorporating technological modules, promoting soft skills, and aligning curricula with global market expectations. The findings suggest that while progress has been made, significant gaps remain between academic preparation and professional realities. Greater collaboration between institutions and industry stakeholders is essential to ensure that future translators are equipped with both the technical and intercultural competencies required in the 21st century. The study highlights the importance of ongoing curriculum reform, critical digital literacy, and lifelong learning in shaping the next generation of translation professionals.